Risk factors for bovine paratuberculosis II. The multiple analysis of risk ractors for bovine paratuberculosis - Çetinkaya, Burhan; Erdo?an, Hidayet M.; Morgan, Kenton L. (Scientific and Technical Research Council of Turkey, 1997)
Farm and management variables that had a P value of 0.25 or less and those that were considered biologically important were offered to logistic regression models. Two different models were constructed : Model I included all the variables and replacement rate was left out of Model II. Channel Island breeds (Jersey and Guernsey), the purchase of replacements privately, the presence of farmed deer and calving in groups were determined to be risk factors for bovine paratuberculosis in logistic regression.
Keywords: Cattle; Farm and management variables; Logistic regression; Paratuberculosis